Analysis of antimicrobial susceptibility pattern of ocular infections at Regional Ophthalmic Institute in India - Nuzhat, Qudsia; Bandyopadhyay, Arkapal; Chaurasia, Rakesh Chandra; Singh, Satya P.; Singh, Monica (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Ocular infections are a result of alteration in the normal microbial flora of eye. They are not only responsible for increase in morbidity varying from self-limiting trivial infection to sight threatening infection but also blindness. Methods: Patients with ocular infections were recruited at Regional Institute of Ophthalmology, Moti Lal Nehru Medical College, Allahabad, Uttar Pradesh. Bacterial profile in ocular infections and susceptibility pattern to commonly used antibiotics were analyzed amongst these patients. The isolated organism was then identified by colony morphology, gram stain and biochemical test following which in vitro susceptibility test was performed by Kirby-Bauer disc diffusion method and interpreted clinically. Results: Staphylococcus aureus and coagulase negative Streptococcus were most common etiological agents of ocular infections in the present study. It was observed that bacterial isolates were highly (in 100% of cases) susceptible to vancomycin and chloramphenicol among gram positive organisms. Gram negative organisms showed higher susceptibility to moxifloxacin, tobramycin and gentamycin. Pseudomonas was seen to have sensitivity towards ceftazidime and cefazolin. Conclusions: The present study gives an insight into use of ocular antimicrobials in northern India. These findings illustrate the need for constant bacterial surveillance before starting empirical treatment.